Comparative evaluation of evening primrose oil and vitamin E on the severity of cyclic Mastalgia: A Systematic Review and Meta-Analysis - Morvarid Irani; Sedigheh Sheidaei; Talat khadivzadeh; Masoumeh Ghazanfarpour; Seyedeh Fatemeh Nosrati (Mashhad University of Medical Sciences, 2020)
Introduction: Many women suffer from mastalgia; this issue is very important due to the importance of proper use of the drug. Due to the complications of chemical drugs, patients tend to use complementary medicine. Therefore, this systematic review was conducted with aim to compare the effects of evening primrose oil and vitamin E on cyclic mastalgia. Methods: In this systematic review and meta-analysis, data related to comparison of evening primrose oil and vitamin E were searched using the key words of mastalgia, evening primrose oil, vitamin E, and breast pain in the Electronic databases of Pubmed, Scopus, Web of science, Magiran, Iran doc, Iran medex, SID, and also Google scholar without time limitation until 2019. Jedad Index was used to evaluate the quality of the studies. Data were analyzed by Comprehensive Meta-analysis Version 2. Results: Among 701 articles found in the initial search, 8 randomized trials with sample volume of 878 participants were selected for this systematic review. The studies were conducted in U.S, India, Pakistan and Iran. The result of meta-analysis showed that the difference between two groups of intervention and control was .311 (95% CI: -0/266 to 0/888) and the difference was not statistically significant (p=0.291); this indicates that the efficacy of Evening promise oil and vitamin E is similar. Conclusion: The efficacy of Evening promise oil and vitamin E in treatment of mastalgia is similar. Given the high heterogeneity of studies, low sample size and the variety of methods for determining the outcome, further studies in this field is recommended.